Sibling abuse trauma: assessment and intervention strategies for children, families, and adults - Caffaro, John V. (Routledge, Taylor & Francis Group, 2014)
"This book describes an integrative, strengths-based approach to individual and family psychotherapy guided by the effects of abuse trauma on the development of sibling relationships. It fills a void in the training and education of family violence professionals and validates sibling experiences as an important part of human development"--